An analytical representation of conformal mapping for genus-zero implicit surfaces and its application to surface shape similarity assessment. (July 2015) - Huang, Shunzhou; Wang, Hao; Zhao, Yong; Lin, Zhongqin
Abstract: This paper develops an analytical representation of conformal mapping for genus-zero implicit surfaces based on algebraic polynomial functions, and its application to surface shape similarity assessment. Generally, the conformal mapping often works as a tool of planar or spherical parameterization for triangle mesh surfaces. It is further exploited for implicit surface matching in this study. The method begins with discretizing one implicit surface by triangle mesh, where a discrete harmonic energy model related to both the mesh and the other implicit surface is established based on a polynomial-function mapping. Then both the zero-center constraint and the landmark constraints are added to the model to ensure the uniqueness of mapping result with the Möbius transformation. By searching optimal polynomial coefficients with the Lagrange–Newton method, the analytical representation of conformal mapping is obtained, which reveals all global and continuous one-to-one correspondent point pairs between two implicit surfaces. Finally, a shape similarity assessment index for (two) implicit surfaces is proposed through calculating the differences of all the shape index values among those corresponding points. The proposed analytical representation method of conformal mapping and the shape assessment index are both verified by the simulation cases for the closed genus-zero implicit surfaces. Experimental results show that the method is effective for genus-zero implicit surfaces, which will offer a new way for object retrieval and manufactured surface inspection. Highlights: We develop an analytical representation of conformal mapping for implicit surfaces. An analytical conformal mapping describes a continuous one-to-one correspondence. Conformal mappings from complex surfaces to simple ones are effectively obtained. Conformal mappings between two similar complex surfaces are effectively obtained.